Male fertility restored by transplanting primordial germ cells into testes: a new way towards efficient transgenesis in chicken - Trefil, Pavel; Aumann, Dorothea; Koslová, Anna; Mucksová, Jitka; Benešová, Barbora; Kalina, Jiří; Wurmser, Christine; Fries, Ruedi; Elleder, Daniel; Schusser, Benjamin; Hejnar, Jiří (Scientific reports, 2017)
The ongoing progress in primordial germ cell derivation and cultivation is opening new ways in reproductive biotechnology. This study tested whether functional sperm cells can be matured from genetically manipulated primordial germ cells after transplantation in adult testes and used to restore fertility. We show that spermatogenesis can be restored after mCherry-expressing or GFP-expressing primordial germ cells are transplantated into the testes of sterilized G0 roosters and that mCherry-positive or GFP-positive non-chimeric transgenic G1 offspring can be efficiently produced. Compared with the existing approaches to primordial germ cell replacement, this new technique eliminates the germ line chimerism of G0 roosters and is, therefore, faster, more efficient and requires fewer animals. Furthermore, this is the only animal model, where the fate of primordial germ cells in infertile recipients can be studied.
Keywords: kur domácí; Transduction, Genetic; Fertility; fenotyp; Male; Phenotype; Cell Transplantation; Chickens; technika přenosu genů; spermatogeneze; Spermatozoa; Spermatogenesis; mužské pohlaví; Testis; fertilita; Animals; zvířata; testis; spermie; transdukce genetická; Gene Transfer Techniques; transplantace buněk